COMPARABILITY OF HBA1C AND LIPIDS MEASURED WITH DRIED BLOOD SPOT VERSUS VENOUS SAMPLES: A SYSTEMATIC REVIEW - Fredrica, (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Diabetes is a major risk factor for cardiovascular disease, which is spreading at an alarming rate over the world, but it is especially widespread in developing nations. The infrastructure and resources required to conduct research are frequently insufficient in these countries, making it difficult to establish the role that dysglycemia and other metabolic risk factors play. DBS samples are now routinely used to evaluate serum antibodies, human immunodeficiency virus (HIV) loads, and blood hormone levels. There is enough evidence to prove the comparability of results between research using DBS samples and those using conventional venous samples. The DBS method appears to hold significant potential for addressing the logistical challenges of venous sampling for research of metabolic risks in resource-constrained situations, but only if standards and calibrations can be agreed upon, as has been done in other fields of study. As a result of the breadth of comparisons provided by our findings, we may conclude that these generalizations are true of data acquired from a variety of different laboratories. There have been reports in the scientific literature concerning findings that are equivalent in terms of the strength of the linkages between DBS assay values and venous sample values. Tests based on DBS samples are clearly related with assays based on standard venous samples for HbA1c and selected blood lipids.